Experimental Evidence for Limited in vivo Virulence of Mycobacterium africanum - Cá, B (2019)
Tuberculosis remains a public health problem and a main cause of death to humans. Both Mycobacterium tuberculosis and Mycobacterium africanum cause tuberculosis. In contrast to M. tuberculosis, which is geographically spread, M. africanum is restricted to West Africa. Differences have also been found in the growth rate and type of disease caused by M. africanum, globally suggesting an attenuation of this bacteria. In this study, we used the mouse model of infection to follow the dynamics of M. africanum infection in terms of bacterial burdens and tissue pathology, as well as the immune response triggered. Our findings support a lower virulence of M. africanum as compared to M. tuberculosis, including in mice lacking IFN-¿, a major protective cytokine in tuberculosis. Furthermore, the lung immune response triggered by M. africanum infection in wild-type animals was characterized by a discrete influx of leukocytes and a modest transcriptional upregulation of inflammatory mediators. Our findings contribute to elucidate the pathogenesis of M. africanum, supporting the hypothesis that this is an attenuated member of the tuberculosis-causing bacteria. Understanding the biology of M. africanum and how it interacts with the host to establish infection will have implications for our knowledge of TB and for the development of novel and better tools to control this devastating disease.